Rating the Efficiency of Regional Health Systems and Compulsory Health Insurance - Russkikn, Tatyana Nikolayevna; Sirotkina, Natalya Valeryevna; Tinyakova, Viktoriya Ivanovna (Economy of Regions, 2015)
In the face of increasing of the regional differentiation of the health systems and compulsory health insurance, the comparative analysis and efficiency assessment of their performance in the context of the subjects of the Russian Federation becomes particularly relevant. Therefore, the research is focused on the regional health systems and compulsory health insurance (CHI), and the subject matter of the study is the analysis of the system performance. In the article, the comparative analysis of the authors’ approaches to the formation of efficiency criteria of the performance of regional health systems and CHI, as well as to the development of a typology of the constituent entities of the Russian Federation based on these criteria is conducted. The authors propose a system of indicators to measure the economic, medical and social efficiency of the systems under consideration. Moreover, a set of indicators of economic efficiency forms two groups of indicators. The first group of indicators reflects the financial performance, and the second - the structural efficiency. A methodological approach to the formation of the rating for subjects of the Russian Federation according to the levels of efficiency, based on the procedures of cluster analysis and fuzzy mathematics are developed. A feature of the proposed approach to the construction of a typology of the subjects in terms of efficiency is the introduction of a reference subject with the national average performance indicators system that allows to qualitatively assess the effectiveness of regional health systems and CHI by comparing them with the «reference subject». The results of the empirical research have indicated a high differentiation of the subjects of the Russian Federation in terms of economic efficiency, have allowed to identify the subjects-outsiders. The theoretical and practical results can be used for the rational choice of priorities of the state policy in the field of the public health and CHI at the federal and regional levels.